( The impact of using e-commerce to improve return on investment in companies (Applied Study on the Public Shareholding Companies listed on the Amman Stock Exchange - Abu Zir, Omran Ishaq; Fares, Iyad Jamal; Al-Atili, Manal Abdel-Rahman (Journal of Economic, Administrative and Legal Sciences, 2018)
This study aimed at identifying the impact of using e-commerce to improve return on investment in companies (Applied Study on the Public Shareholding Companies listed on the Amman Stock Exchange), as well as the impact of the application of e-commerce on its performance, in addition to recognizing the impact of some financial variables such as size, And retained earnings on the performance of those companies. The sample of the study was selected on the basis of the seventy-four companies listed on the Amman Stock Exchange. One questionnaire was distributed to each company and the financial managers were targeted or appointed in the administrative departments. The sample was valid for sixty-seven companies (91%).The analysis of multiple linear regression and Pearson correlation coefficient was used to achieve the desired results of the study objectives. A number of results were obtained. The most important of these results is that the structure of ownership does not have a statistically significant effect on the financial performance of these companies. On the financial performance of these companies, in addition to the existence of a relationship of statistical significance of the control variables of the size and financial increase on the financial performance of those companies, while there was no significant impact of the retained earnings on financial performance.
Keywords: e-commerce; improving return on investment; financial performance